THE COMBAT EFFECTIVENESS OF THE MANAGEMENT BODIES OF THE STATE SPECIAL TRANSPORT SERVICE DURING THEIR TRANSITION FROM PEACE FOOTING TO MARTIAL LAW - Malkov, M. I.; Radkevych, A. V.; Stepanenko, O. O. (Science and Transport Progress, 2007)
The article studies dependence of production capabilities losses on the efficiency of managing bodies and on this basis developes a method of individual qualification assessment of the officials and determination of the professional level of the managing body as a whole, taking into account the significance of its structural elements.